Inhibition of lytic polysaccharide monooxygenase by natural plant extracts. Issue 3 (31st August 2021) - Tokin, Radina; Frandsen, Kristian E. H.; Ipsen, Johan Ørskov; Lo Leggio, Leila; Poojary, Mahesha M.; Berrin, Jean‐Guy; Grisel, Sacha; Brander, Søren; Jensen, Poul Erik; Johansen, Katja Salomon
Summary: Lytic polysaccharide monooxygenases (LPMOs) are monocopper enzymes of industrial and biological importance. In particular, LPMOs play important roles in fungal lifestyle. No inhibitors of LPMOs have yet been reported. In this study, a diverse library of 100 plant extracts was screened for LPMO activity‐modulating effects. By employing protein crystallography and LC–MS, we successfully identified a natural LPMO inhibitor. Extract screening revealed a significant LPMO inhibition by methanolic extract of Cinnamomum cassia (cinnamon), which inhibited Ls AA9A LPMO from Lentinus similis in a concentration‐dependent manner. With a notable exception, other microbial LPMOs from families AA9 and AA10 were also inhibited by this cinnamon extract. The polyphenol cinnamtannin B1 was identified as the inhibitory component by crystallography. Cinnamtannin B1 was bound to the surface of Ls AA9A at two distinct binding sites: one close to the active site and another at a pocket on the opposite side of the protein. Independent characterization of cinnamon extract by LC–MS and subsequent activity measurements confirmed that the compound inhibiting Ls AA9A was cinnamtannin B1. The results of this study show that specific natural LPMO inhibitors of plant origin exist in nature, providing the opportunity for future exploitation of such compounds within various biotechnological contexts.